Pendekatan Multikultural menuju Pemahaman Agama yang Plural - Zainuddin, M. (UIN Maulana Malik Ibrahim Malang, 2005)
We have the expectation of the birth of change which makes our life blissful. Among the educators and the intellects, a new awareness is now there for growing and developing the open-mindedness (inclusive) on religion comprehension. The birth of intellectual thinking of transformative Islam, liberal, inclusive, contextual, and many other terms whatsoever are the new era for desecration of the thought of Islam (alla taqsidiyyah). Moreover, the contemporary liberal-inclusive thoughts such as Hassan Hanafi, Arkoun, al Jabiri, al Naim, and so forth were already introduced to the young intellects generation in Indonesia. This article discusses about the absolute claims of some religions and also multicultural approach to create the harmony life among people with different religions. Kita masih memiliki harapan akan lahirnya perubahan yang menggembirakan. Di kalangan akademisi dan intelektual kita, kini telah muncul ‘kesadaran baru’ bagi tumbuh dan berkembangnya pemikiran terbuka (inklusif) dalam pemahaman agama. Munculnya pemikiran intelektual Islam transformative, liberal, inklusif, kontekstual, dan apapun istilahnya merupakan era baru bagi desakralisasi pemikran Islam (alla taqdisiyyah). Apalagi kemudian pemikiran-pemikiran kontemporer liberal-inklusif seperti Hassan Hanafi, Arkoun, al Jabiri, al Naim, dan seterusnya telah disosialisasikan oleh generasi intelektual muda di Indonesia. Artikel ini membahas klai-klaim absolut dari beberapa agama dan juga pendekatan multicultural untuk menciptakan kehidupan harmonis di kalangan umat beragama.